Efficacy of a spot-on formulation containing moxidectin 2.5%/imidacloprid 10% for the treatment of Cercopithifilaria spp. and Onchocerca lupi microfilariae in naturally infected dogs from Portugal - Otranto, Domenico (2021)
Funding Information: The authors are grateful to Giada Annoscia and Riccardo Paolo Lia (Department of Veterinary Medicine, University of Bari, Italy) for their support during molecular identification and morphometric determination of the parasites. Funding Information: This study has been partially funded by Elanco Animal Health, Monheim, Germany. Publisher Copyright: © 2021, The Author(s).